TLR4 polymorphisms seem not to be associated with prediabetes and type 2 diabetes but predispose to diabetic retinopathy; TLR4 polymorphisms in glucose continuum - Zaharieva ET; Kamenov ZA; Savov AS (Endocrine Regulations, 2017)
Objectives. Compared to type 1 diabetes, the role of the immune and autoimmune pathogenetic mechanisms is much less studied in the type 2 diabetes. Toll-like receptors 4 (TLR4) have a leading role in inflammation, insulin resistance, and vascular damage. This study aimed to analyze the relationship between the polymorphisms in TLR4 gene and different stages in the glucose continuum from prediabetes to the type 2 diabetes and chronic microvascular complications.